2017
DOI: 10.1016/j.jneuroim.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen protection against EAE modulates the microbiota and mucosal-associated regulatory cells

Abstract: Sex hormones promote immunoregulatory effects on multiple sclerosis. In the current study we evaluated the composition of the gut microbiota and the mucosal-associated regulatory cells in estrogen or sham treated female mice before and after autoimmune encephalomyelitis (EAE) induction. Treatment with pregnancy levels of estrogen induces changes in the composition and diversity of gut microbiota. Additionally, estrogen prevents EAE-associated changes in the gut microbiota and might promote the enrichment of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 60 publications
2
34
2
Order By: Relevance
“…134 Treatment with pregnancy levels of estrogen induces changes in the composition and diversity of the gut microbiota, associated with protection against EAE. 135 It was shown that while EAE led to dysbiosis in mice, pretreatment with estrogen reduced these changes and increased regulatory B-cell and anti-inflammatory macrophage numbers in mesenteric lymph nodes and in the spinal cord. 135 Vitamin D (D3) is an environmental factor that may be involved in the development of autoimmunity.…”
Section: Interaction Between Hormonal and Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…134 Treatment with pregnancy levels of estrogen induces changes in the composition and diversity of the gut microbiota, associated with protection against EAE. 135 It was shown that while EAE led to dysbiosis in mice, pretreatment with estrogen reduced these changes and increased regulatory B-cell and anti-inflammatory macrophage numbers in mesenteric lymph nodes and in the spinal cord. 135 Vitamin D (D3) is an environmental factor that may be involved in the development of autoimmunity.…”
Section: Interaction Between Hormonal and Environmental Factorsmentioning
confidence: 99%
“…135 It was shown that while EAE led to dysbiosis in mice, pretreatment with estrogen reduced these changes and increased regulatory B-cell and anti-inflammatory macrophage numbers in mesenteric lymph nodes and in the spinal cord. 135 Vitamin D (D3) is an environmental factor that may be involved in the development of autoimmunity. Sun protection behavior, which has increased in recent decades, has significantly reduced the hours of light exposure in the population at large.…”
Section: Interaction Between Hormonal and Environmental Factorsmentioning
confidence: 99%
“…Many mechanisms remain undefined or even unidentified. Estrogen prevents changes in gut microbiota associated with EAE [81]. Such mechanisms may include the promotion of specific gut microbiota, and the cross talk between the gut microbiota and sex hormones may help immune-regulation resulting in neuroprotection.…”
Section: Role Of Sex Hormones In Remyelinationmentioning
confidence: 99%
“…The present findings provide evidence that the modulation of gut microbiota is another mechanism by which E2 mediates energy homeostasis. While E2 was associated with a decrease in the gut microbial evenness in the current study, an increase in microbial diversity has been reported in cycling rats and E2-treated female mice [38, 73]. These differences across studies could be due to fluctuating estrogens and other ovarian hormones in the cycling rats and/or species differences [38], and a much higher dose of estradiol (2.5 mg/day, consistent with levels at pregnancy) used in the mice [73].…”
Section: Discussionmentioning
confidence: 48%
“…While E2 was associated with a decrease in the gut microbial evenness in the current study, an increase in microbial diversity has been reported in cycling rats and E2-treated female mice [38, 73]. These differences across studies could be due to fluctuating estrogens and other ovarian hormones in the cycling rats and/or species differences [38], and a much higher dose of estradiol (2.5 mg/day, consistent with levels at pregnancy) used in the mice [73]. Alternatively, while a lower microbial diversity is usually associated with obesity and metabolic disorders [74, 75], a change in relative abundance without any changes in microbial richness or evenness can also alter microbial homeostasis [45].…”
Section: Discussionmentioning
confidence: 48%